Sec71 functions as a GEF for the small GTPase Arf1 to govern dendrite pruning of Drosophila sensory neurons - Wang, Yan (2017)
Pruning, whereby neurons eliminate their excess neurites, is central for the maturation of the nervous system. In Drosophila, sensory neurons, ddaCs, selectively prune their larval dendrites without affecting their axons during metamorphosis. However, it is unknown whether the secretory pathway plays a role in dendrite pruning. Here, we show that the small GTPase Arf1, an important regulator of the secretory pathway, is specifically required for dendrite pruning of ddaC/D/E sensory neurons but dispensable for apoptosis of ddaF neurons. Analyses of the GTP- and GDP-locked forms of Arf1 indicate that the cycling of Arf1 between GDP-bound and GTP-bound forms is essential for dendrite pruning. We further identified Sec71 as a guanine nucleotide exchange factor for Arf1 that preferentially interacts with its GDP-bound form. Like Arf1, Sec71 is also important for dendrite pruning, but not for apoptosis, of sensory neurons. Arf1 and Sec71 are interdependent for their localizations on Golgi. Finally, we show that the Sec71/Arf1-mediated trafficking process is a prerequisite for Rab5-dependent endocytosis to facilitate endocytosis and degradation of the cell-adhesion molecule Neuroglian (Nrg).